Generation of human induced pluripotent stem cells from adipose-derived stromal/stem cells isolated from a 75-year-old patient - Stoyanova, Elena; Oreshkova, Tsvetelina; Mourdjeva, Milena (Archives of Biological Sciences, 2017)
Human adipose-derived stromal/stem cells (hASCs) have been considered a valuable cell source for generating induced pluripotent stem cells (iPSCs). Adipose tissue is easy to obtain. Moreover, the isolated cells rapidly proliferate to reach the required number of cells. Some authors have already shown that iPSCs can be successfully obtained using adult hASCs. Nevertheless, little is known about the generation of iPSCs using hASCs isolated from the tissues of patients over the age of 70. In this study, we examined the generation of iPSCs from hASCs isolated from a 75-year-old man. We transduced hASCs with human transcription factors OCT4, SOX2, c-MYC and KLF4 and observed the formation of human embryonic stem cell (hESC)-like colonies. The efficiency of the reprogramming process was 0.08% at day 18 post-infection. Reprogrammed cells expressed pluripotent state-specific transcription factors OCT4, SOX2, NANOG and KLF4, and were able to differentiate into three germ layers in vitro. https://doi.org/10.2298/ABS170313018S Received: March 13, 2017; Revised: May 10, 2017; Accepted: May 17, 2017; Published online: June 6; 2017 How to cite this article: Stoyanova E, Oreshkova T, Mourdjeva M. Generation of human induced pluripotent stem cells from adipose-derived stromal/stem cells isolated from a 75-year-old patient. Arch Biol Sci. 2017;69(4):715-21.